Calcineurin inhibitors augment endothelial-to-mesenchymal transition by enhancing proliferation in association with cytokine-mediated activation - Woda, Craig B.; Bruneau, Sarah; Mak, Anne Linde; Haskova, Zdenka; Liu, Kaifeng; Ghosh, Chandra C.; Briscoe, David M. (Biochemical and biophysical research communications, 2019)
Calcineurin Inhibitors (CNIs) are routinely used for immunosuppression following solid organ transplantation. However, the prolonged use of these agents lead to organ fibrosis which limits their efficacy. CNIs induce TGFβ expression, which is reported to augment endothelial-to-mesenchymal transition (EndMT), but their role in this process is not known. In these studies, we find that the CNIs FK506 and cyclosporine (CsA) are potent to increase endothelial cell (EC) proliferation using established in vitro assays (P < 0.05). Furthermore, using phosphokinase arrays, we find that each CNI activates the MAPK and Akt/mTOR signaling pathways, and that pharmacological inhibition of each pathway targets CNI-induced proliferative responses (P < 0.001). EndMT was evaluated by FACS for N-cadherin and CD31 expression and by qPCR for the expression of α-smooth muscle actin, N-cadherin and Snail. We find that CNIs do not directly induce dedifferentiation, while TGFβ and hypoxia induce EndMT in small numbers of EC. In contrast, the treatment of EC with the inflammatory cytokine TNFα was potent to elicit an EndMT response, and its effects were most notably in EC following proliferation/doubling. Taken together, these observations suggest that CNIs elicit proliferative responses, which enhance EndMT in association with local inflammation. The clinical implications of these findings are that anti-proliferative therapeutics have high potential to target the initiation of this EndMT response. •Calcineurin inhibitors stimulate endothelial cell proliferation and angiogenesis.•The inflammatory cytokine TNFα is potent to elicit an EndMT response.•Endothelial cell doubling markedly increases susceptibility to TNFα-induced EndMT.